2010
DOI: 10.2119/molmed.2010.00028
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Interleukin-18 Aggravates Cardiac Fibrosis and Diastolic Dysfunction in Fructose-Fed Rats

Abstract: Inflammation plays an important role in the pathophysiology of the metabolic syndrome (MS). We determined whether the overexpression of interleukin (IL)-18 could aggravate left ventricular (LV) remodeling and diastolic dysfunction in fructose-fed rats (FFRs). To create an animal model for MS, male Wistar rats received 10% fructose in water for 8 months. We used an adenovirus encoding rat IL-18 to overexpress IL-18 in FFRs by intravenous administration. IL-18 overexpression led to increases in collagen volume f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
16
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 23 publications
6
16
0
1
Order By: Relevance
“…We did not find impaired active relaxation as judged from the left ventricular relaxation constant (Tau), values being comparable to those reported for healthy male rats (Xing et al. ). Endothelial dysfunction and diastolic dysfunction has been demonstrated in studies using intact female DSS rats treated with high salt at young age and for a duration of 12 months (Adams et al.…”
Section: Discussionsupporting
confidence: 89%
“…We did not find impaired active relaxation as judged from the left ventricular relaxation constant (Tau), values being comparable to those reported for healthy male rats (Xing et al. ). Endothelial dysfunction and diastolic dysfunction has been demonstrated in studies using intact female DSS rats treated with high salt at young age and for a duration of 12 months (Adams et al.…”
Section: Discussionsupporting
confidence: 89%
“…Other authors found similar results after submitting Wistar rats to 10% fructose overload for eight weeks (17). …”
Section: Discussionsupporting
confidence: 63%
“…Other researchers have found similar results for Wistar rats receiving a 10% fructose overload for 8 weeks [93]. …”
Section: Introductionsupporting
confidence: 75%